Scoping review of the literature to ascertain how follow-up care is provided to major trauma patients post discharge from acute care - Andrea P Marshall; Jamie Ranse; Elizabeth Wake (BMJ Open, 2022)
Objectives Survival following traumatic injury has increased, requiring ongoing patient follow-up. While longitudinal outcomes of trauma patients are reported, little is known about optimal delivery of follow-up service for this group. The aim of this scoping review was to identify and describe the structure, process and outcomes of postdischarge follow-up services for patients who sustained major trauma.Evidence review This scoping review was conducted by searching CINAHL, MEDLINE and EMBASE databases. Articles were screened by three independent reviewers. The data of selected articles were organised in the categories of the Donabedian quality framework: structure, processes and outcomes.Results Twenty-six articles were included after screening by title/abstract then full text against the inclusion/exclusion criteria; 92% (n=24) were from the USA.Follow-up services were provided by designated trauma centres and delivered by a mixture of health disciplines. Delivery of follow-up was multimodal (in person/telehealth). Protocols and guidelines helped to deliver follow-up care for non-physician led services.Ongoing health issues including missed injuries, pain and infection were identified. No standardised criteria were established to determine recipients, the timing or frequency of follow-up was identified. Patients who engaged with follow-up services were more likely to participate in other health services. Patients reported satisfaction with follow-up care.Conclusion There are wide variations in how follow-up services for major trauma patients are provided. Further evaluation should focus on patient, family and organisational outcomes. Identifying who is most likely to benefit, when and how follow-up care is delivered are important next steps in improving outcomes.